Association between 19 dietary fatty acids intake and rheumatoid arthritis: Results of a nationwide survey. (January 2023) - Xie, Ruijie; Zhang, Ya
Highlights: We investigated for the first time the relationship between the intake of 19 different dietary fatty acids and rheumatoid arthritis in a relatively large sample size of the population. Among the 19 dietary fatty acids, only 4 subclasses (hexadecanoic acid, octadecanoic acid, hexadecenoic acid, and docosahexaenoic acid) were significantly associated with Hs-CRP or RA risk. We found the inverted U-shaped relationship between MUFAs and RA risk, which may provide insights for future interventional studies to find potential treatment or prevention strategies for RA. Abstract: Background: The relationship between dietary fatty acid intakes and rheumatoid arthritis (RA) is unclear and the available studies have focused on only a few fatty acids. This study investigated the association between the intake of 19 dietary fatty acids and RA in U.S. adults. Methods: This cross-sectional study using nationally representative data from the 2010-2020 National Health and Nutrition Examination Survey (NHANES). Multivariate linear regression model, multivariate logic regression models, smoothing curve fitting, and two-segment linear regression model were used to explore the relationships between 19 dietary fatty acids intakes with high-sensitivity C-reactive protein (Hs-CRP) and RA risk. Results: A total of 16, 530 participants were included (1053 participants with RA). Intake of hexadecanoic acid and octadecanoic acid were significantly associated with higher Hs-CRP levels, intake of hexadecenoic acid was significantly associated with higher RA risk, and intake of docosahexaenoic acid was significantly associated with lower RA risk. In addition, there was an inverted U-shaped relationship between total monounsaturated fatty acids (MUFAs) intake and RA risk, with the inflection point reached at 15.77% . Conclusions: Among the 19 dietary fatty acids, only 4 subclasses were significantly associated with Hs-CRP or RA risk. The inverted U-shaped relationship between MUFAs and RA risk may provide insights to find potential prevention strategies for RA.